Polyoxometalate-Based Lanthanide Complexes: Insights into the Design and Structural Control Based on Multivariate Analysis - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Canon-Mancisidor, W; Canon-Mancisidor, W (John Wiley and Sons Inc, 2025)
Two novel lanthanide-based complexes, [NBu4]3[YbH(PW11O39)(phen)2]·H2O (LM4–UBO–1–Yb) and K13[Dy(SiW11O39)2]·21H2O (LM4–UBO–2–Dy), are synthesized and characterized to explore how Keggin monolacunary polyoxometalates (KMLPOMs) affect LnIII geometry. SHAPE analysis shows both complexes adopt square antiprismatic (SAPR) geometries with pseudo-D4d symmetry. LM4–UBO–1–Yb has a slightly distorted SAPR geometry, with a displacement parameter (D) of 1.068 Å, influenced by organic ligands, while LM4–UBO–2–Dy is more rigid (D = 1.298 Å). A structural multivariate analysis of 185 KMLPOM-based LnIII complexes identifies four main types: mononuclear inorganic, mononuclear hybrid, dinuclear hybrid, and dinuclear inorganic. Structural trends reveal that [BW11O39]9− and [PW11O39]7− prefer SAPR geometries, while [GeW11O39]8− and [SiW11O39]8− favor bicapped trigonal prism (BTPR) geometries. D values below ≈1.10 Å are linked to BTPR geometries, while higher values align with SAPR geometries. This study highlights the heteroatom s ionic radius as a key factor in determining geometry and offers predictive guidelines for designing LnIII-KMLPOM systems. © 2025 Wiley-VCH GmbH.